Accentuating English Language as the Sole Medium of Pedagogy in South Africa: Issues and Perspectives - Odeku, Kola. O. (Global Media Journal, 2018)
South Africa is a multilingual country where eleven official languages are constitutionally entrenched and guaranteed. These languages have equal footing in all activities, including as a medium of teaching and learning at schools. This is the reality and the owners of these languages are very cautious of them and as such guide them jealously. This article argues that while it is constitutionally expedient to recognize and protect the eleven official languages, especially the indigenous ones, all of them cannot be used at the same time as medium of teaching and learning. Against this backdrop, this article emphasis that English, which is one of the official languages recognized in the South African Constitution and at the same time widely understood by other groups and worldwide should be singled out and be adopted as the medium of instruction and education in all schools.
Article published in the Global Media Journal vol 16 (31)
Keywords: Language of instruction; Pedagogy; Education; Competency; Learners; English language; English - Accents and accentuation; English language -Study and teaching --South Africa